Nutrient Uptake of Two Semidomesticated Jaltomata Schltdl. Species for Their Cultivation - Ignacio Darío Flores-Sánchez; Manuel Sandoval-Villa; Ebandro Uscanga-Mortera (Plants)
The nutrient uptake of a species under cultivated conditions is important for program fertilization. The Jaltomata genus has two semidomesticated species, J. procumbens and J. tlaxcala, used as food and considered with potential for their study in controlled environments. The objective of this research was to determine nutrient uptake curves of these species in a greenhouse and using hydroponics. The research was carried out at the Colegio de Postgraduados, Campus Montecillo, Texcoco, State of Mexico, from August to November 2020. The treatments included the following: two species and three electrical conductivity levels: 1, 2, and 3 dS m−1. Nutrients in leaf and total dry matter (TDM) were determined. Variability between species and phenological stages on the nutrient concentration and accumulation of TDM was observed. For macronutrients, J. procumbens concentrated in descending order more P from the vegetative stage (4.21–2.43 g kg−1 dry matter), and Mg until fructification (4.92–3.26 g kg−1 dry matter), for K it was higher at vegetative (52.29 g kg−1 dry matter) and harvesting stages (26.05 g kg−1 dry matter), and N (23.92 g kg−1 dry matter) at flowering; J. tlaxcala concentrated more Ca from fructification (10.10–13.85 g kg−1 dry matter). For micronutrients, J. tlaxcala concentrated more Fe from the vegetative stage (157.7–207.5 mg kg−1 dry matter), B and Zn at 23.3–38.4 and 26.04–28.45 mg kg−1 dry matter, respectively, from flowering, and Mn (108.4–232.28 mg kg−1 dry matter) from fructification. The main structures of TDM accumulation by vegetative stage in J. procumbens were the leaf and root (vegetative and flowering), root and stem (fructification), and reproductive structures and root (harvesting); in J. tlaxcala, the main structures were the leaf and root (vegetative), root and leaf (flowering and fructification), and root and reproductive structures (harvesting). Due to this variability, specific fertilization programs are required for each species.